Analisis Dampak Usaha Kain Tenun Subi Donggala terhadap Ekonomi Masyarakat Kelurahan Pantoloan Boya Kecamatan Tawaeli Kota Palu - Moh. Rizki; Moh. Rafli; Mohamad Raihan; Destiny Putri Izmi (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
MSMEs play a crucial role in the economy, and Tenun Subi Donggala, as a cultural heritage, holds significant aesthetic and economic value. Artisans in Pantoloan Boya Village face challenges such as poor marketing, low technological knowledge, and limited government support. Using a qualitative descriptive approach, this research found that while this business adds to family income, the average income remains low. To develop the potential of this business, training, access to stable raw materials, marketing strategies, and government support are needed. Tenun Subi Donggala remains a symbol of economic optimism and the preservation of local culture.